Identification of agility predictors in basketball - Horička, Pavol; Šimonek, Jaromír (Akademia Wychowania Fizycznego w Poznaniu)
Aim of Study. This study aims at finding out the existence and character of determining factors of agility performance. Material and Methods. Individual types of agility performance (Illinois test, Fitro agility check, modified Y-test), reaction and acceleration speed (10 m dash) and cyclic running speed (30 m run), spatial orientation (shuttle run) were diagnosed in the selected sample of basketball players in order to identify agility predictors. The sample consisted of 12 players of top female basketball team BKM UKF Nitra, Slovakia (n = 12). Agility score was calculated using the device Fitro agility check (FAC), time was measured using the Witty time measurement instrument and lighting device WittySem traffic light. The level of cognitive abilitieswas detected by means of the Stroop test. Spearman correlationwas used for the assessment of the relationship among all three levels of agility performance (Illinois test, Y agility test, Fitro agility test) and other indicators. Results. In case of simple agility performance, the correlation analysis showed (change of direction speed; CODS, Illiois test) significant correlation with reactive agility, acceleration speed and also simple reactive agility. In case of complex reactive agility, significant correlation was found with pre-planned (running) agility (Illinois); simple reactive agility (Y-test) and cognitive abilities (Stroop test). The factor of acceleration speed (ACC – 3 m) showed greatest share (71.5%) in the reactive agility performance of basketball players of the selected sample. Conclusions. Our findings suggest that COD and RA are two different and independent skills. The share of motor predictors of agility performance decreases with the complexity of agility, while the share of mental cognitive factors on the cultivation of agility increases.
Keywords: basketball; cognitive abilities; pre-planned agility; reactive agility